The Ending of Time - Jiddu Krishnamurti (Krishnamurti Foundation India, 1985)
This very important work offers penetrating dialogues between the great spiritual leader and the renowned physicist that shed light on the fundamental nature of existence. Krishnamurti and David Bohm probe such questions as 'why has humanity made thought so important in every aspect of life? How does one cleanse the mind of the 'accumulation of time' and break the 'pattern of ego -centered activity'?The Ending of Time concludes by referring to the wrong turn humanity has taken, but does not see this as something from which there is no escape. There is an insistence that mankind can change fundamentally; but this requires going from one's narrow and particular interests toward the general, and ultimately moving still deeper into that purity of compassion, love and intelligence that originates beyond thought, time, or even emptiness.